Adaptability and Stability of Safflower Genotypes for Oil Production - de Oliveira Neto, Sebastião Soares [UNESP]; Zeffa, Douglas Mariani; Freiria, Gustavo Henrique; Zoz, Tiago; da Silva, Carlos Jorge; Zanotto, Maurício Dutra [UNESP]; Sobrinho, Renato Lustosa; Alamri, Saud A.; Okla, Mohammad K.; Abdelgawad, Hamada (MDPI, 2022)
The study aimed to analyze the agronomic performance of 11 safflower genotypes using adaptability and stability methods, while identifying safflower genotypes with stable behavior and a high grain yield in different environments of the Brazilian Cerrado. Ten lines and a cultivar of safflower were evaluated in four environments in the Brazilian conditions. Our results revealed the genotypes P30, P35, P9, P11, and P31 to be superior for grain yield and P43, P7, P11, and P31 to be superior for oil content. The lowest Wricke index, an indication of genotype stability, was observed for P9 (0.41%), which is considered the most stable genotype, followed by P35 (1.29%) and P31 (1.98%). For the predictability of the behavior of genotypes in the environments, P7 (80.85%), P35 (86.10%), P31 (85.90%), and P9 (97.42%) were considered predictable genotypes. The genotypes P11 (1045.6 kg ha−1 and 19.7%) and P21 (952.7 kg ha−1 and 20.6%) are recommended for cultivation in this region, considering both their grain yield and oil content. Safflower is viable to use out of season in the Brazilian Cerrado. The crop can generate profits for farmers and be used for oil production in periods of uncertain corn production.
Keywords: Agroecosystem diversification; Biodiversity; Carthamus tinctorius L; Cerrado crops; Mixed models; Oilseed breeding; Parametric/non-parametric measures